PENGARUH HARGA TERHADAP VOLUME PENJUALAN PEDADANG AYAM PEDAGING PADA PASAR SIMPANG BARU TAMPAN PEKANBARU - Herman, Herman (Sekolah Tinggi Ilmu Ekonomi Riau, 2016)
The problem in this research is that level of sales traders of chicken for three month always experience. The purpose of this study is to determine how much influence the price to sales volume traders on the market broiler intersection Tampan-Pekanbaru. Time this study is three months which serve a population that is ninety-one days. And sampling is to the overall population. Analiysis of the data used is simple inier regression, statistical test. The research concludes that the selling price of a significant and negative impact on sales volume. The amount of influence of independent variables on the dependent variable 60.3 percent and the remaining 39.7 percent are affected by other variables.